Post-War Air Quality Index in Mosul City, Iraq: Does War Still Have an Impact on Air Quality Today? - Zena Altahaan; Daniel Dobslaw (Atmosphere)
The air quality in Mosul was adversely affected both directly and indirectly during and after the conflict phase, spanning from the occupation to the liberation of the city from ISIS (2014–2017). Direct impacts included the ignition of oil fields and sulphur deposits, as well as the use of military weapons and their propellants. Indirectly, the air quality was also compromised by various other factors negatively affecting the quality due to excessive emission levels of air pollutants, such as particulate matter (PM), sulphur dioxide (SO2), nitrogen dioxide (NO2) and other toxic gases. Six important locations in the city of Mosul were selected, and the concentrations of the parameters PM2.5, PM10, formaldehyde (HCHO), total volatile organic compounds (TVOC), NO2 and SO2 were determined at monthly intervals during the year 2022. The sites were selected both according to their proximity and their specific distance from the direct conflict zone. The aim was to assess the present pollutant levels based on WHO guidelines and to compare the results with previous pre-war studies to understand the long-term war impact on air quality. The results showed that the annual average values of PM2.5, PM10 and NO2 were above the WHO limits at all locations throughout the year. In contrast, the annual average values of TVOC, HCHO and SO2 were within the limits in the hot months but exceeded them in the cold months (December to March), which can be attributed to the use of heating material in winter. Two sites revealed higher pollution levels than the others, which can be attributed to their proximity to the devastated areas (conflict zones), high traffic density and a high density of power generators. These factors were further exacerbated by post-war migration from the destroyed and unsafe areas. Thus, in addition to the short-term effects of burning oil fields and sulphur deposits, as well as airborne weapon emissions, the increase in traffic, the use of decentralized power generators, and the higher demand for heating oil, progressive desertification due to deforestation and the destruction of extensive green areas, as well as increasing and unaddressed environmental violations in general, can be held responsible for declining air quality in the urban area. This work should be considered as preliminary work to emphasise the urgent need for conventional air quality monitoring to consolidate air quality data and monitor the effectiveness of different approaches to mitigate war-related air quality deterioration. Possible approaches include the implementation of air purification technologies, the preservation of existing ecosystems, the replacement of fossil energy sources with renewable energy options, proactive and sustainable urban planning and enforcing strict air quality regulations and policies to control and reduce pollution levels.